The prodigal God : recovering the heart of the Christian faith - Keller, Timothy, 1950- (Dutton, 2008)
Uses the biblical tale of the prodigal son to provide both an introduction to Christianity and a clarifying primer on the nature of the gospel for believers, in a resource that reveals how Jesus's essential message is revealed by the story in ways that can enable greater understandings of the Christian faith.